Vibrational Energy Flow Models of Finite Orthotropic Plates - Do-Hyun Park; Suk-Yoon Hong; Hyun-Gwon Kil (Shock and Vibration)
In this paper energy flow models for the transverse vibration of finite orthotropic plates are developed. These models are expressed with time- and locally space-averaged far-field energy density, and show more general forms than the conventional EFA models for isotropic plates. To verify the accuracy of the developed models, numerical analyses are performed for finite rectangular plates vibrating at a single frequency, and the calculated results expressed with the energy and intensity levels are compared with those of classical models by changing the frequency and the damping.